A Versatile Molecular Probe of Napthalimide-Derivative for Zn(II) Sensor: A Mini-Review - Das, Pragyan Parimita; Mohanty, Patitapaban; Barick, Aruna Kumar; Mohapatra, Priyaranjan; Jali, Bigyan Ranjan (Trends in Sciences, 2023)
In recent years, many more chemists have been focused on fluorescent probe research, and significant progresses, which has been made in terms of design and use. This review begins with a brief overview of the most prevalent chemosensor design concepts, followed by a discussion of the photophysical characteristics of the 1,8-naphthalimide structure, such as great photostability, high fluorescence quantum yield and ease of modification which has been used in Zn2+ cation sensing to date. The contributions of the fluorescent probes built on the 1,8-naphthalimide based platform in the field of chemical sensing, biological sensing, pharmaceutical chemistry, environment and food safety in the last 10 years are then systematically introduced by discussing the probe’s fluorescence behavior in the corresponding recognition process. Simultaneously, we intend to build an overall review on fluorescent chemical sensor that will be able to play larger and more interesting role in the future. HIGHLIGHTS Napthalimide-based fluorescence molecular probes for zinc(II) detections are described Various napthalimide derivatives are described based on their potent applications Fluorescence chemosensors are described GRAPHICAL ABSTRACT